2008
DOI: 10.1007/s12275-008-0134-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of exopolysaccharide (EPS) produced by Weissella hellenica SKkimchi3 isolated from kimchi

Abstract: Weissella hellenica SKkimchi3 produces the higher exopolysaccharide (EPS) on sucrose than lactose, glucose, and fructose at pH 5 and 20 degrees C. Sucrose was exclusively used to cultivate SKkimchi3 in all experiments base on the EPS production tests. The molecular mass of EPS, as determined by gel permeation chroma-tography, was 203,000. (1)H and (13)C NMR analysis indicated that the identity of EPS may be a glucan. When EPS, starch, and cellulose was treated with a-amylase, glucoamylase, glucosidase, and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Interestingly, W. hellinica, L. sakei, and L. graminis have been commonly isolated from jeotgal and kimchi, Korean fermented foods. 4,37) In the previous study concerning jeotgal, the pyrosequencing analysis of various jeotgal microbiota showed that Lactobacillus and Weissella were representative genera of the jeotgal bacterial community. 38) The16S rRNA gene clone library method showed L. sakei as the most dominant species among one of the bacterial communities of Ayu-narezushi, Japanese fermented seafood, from two different manufacturers.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, W. hellinica, L. sakei, and L. graminis have been commonly isolated from jeotgal and kimchi, Korean fermented foods. 4,37) In the previous study concerning jeotgal, the pyrosequencing analysis of various jeotgal microbiota showed that Lactobacillus and Weissella were representative genera of the jeotgal bacterial community. 38) The16S rRNA gene clone library method showed L. sakei as the most dominant species among one of the bacterial communities of Ayu-narezushi, Japanese fermented seafood, from two different manufacturers.…”
Section: Discussionmentioning
confidence: 98%
“…This research demonstrated that up to 0.3% β-glucan could be added to yogurt, which meets the nutrient guidelines for added nutritional benefits, without affecting the characteristics of yogurt significantly. The solidification of milk using glucansucrase produced by Leuconostoc species was previously observed by Kim et al [18,19] when the W. hellenica SKKimchi3 strain and Lac. lactis EG001 were cultivated in an MRS medium where 10% sucrose was added to skim milk.…”
Section: Application Of the Dsrlm34 For The Solidification Of Sucrosementioning
confidence: 63%
“…However, the solidification of semi-skimmed milk using glucansucrases has an advantage in minimizing the heat-induced changes and the starter and lactic acid bacteria survival during drying. Few studies on exopolysaccharide produced by lactic acid bacteria isolated from kimchi have been reported [18][19][20]. However, food industry studies on the solidification of milk using glucansucrase produced by Leuconostoc species isolated from kimchi have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Weissella hellenica is a lactic acid bacterial species that is usually found in flounder intestine (Cai et al, 1998), kimchi (Kim et al, 2008), meat and meat products, and pickles, as well as some other sources. W. hellenica exhibits high antimicrobial activity by producing a bacteriocin called weissellicin that acts against pathogenic bacteria (Masuda et al, 2012).…”
Section: Bangladesh Journal Of Scientific and Industrial Researchmentioning
confidence: 99%